0089 Predicting working beyond retirement in the netherlands: an interdisciplinary approach involving occupational epidemiology and economics. (21st August 2017) - Boot, Cécile; Scharn, Micky; Wind, Astrid de; Geuskens, Goedele; Huisman, Martijn; Lindeboom, Maarten; Beek, Allard Van der
Abstract : Objectives: No study so far has combined register-based socioeconomic information with self-reported information on health, demographics, work characteristics and social environment in one study. The aim of this study is to investigate whether socioeconomic, health, demographic, work characteristics and social environmental characteristics independently predict working beyond retirement. Methods: Questionnaire data from the Study on Transitions in Employment, Ability and Motivation was linked to data from Statistics Netherlands. A prediction model was built consisting of the following blocks: socioeconomic, health, demographic, work characteristics and social environment. First, univariate analyses were performed (p<0.15), followed by correlations and logistic multivariate regression analyses with backward selection per block (p<0.15). All remaining factors were combined into one final model (p<0.05). Internal validation was performed. Results: In the final model, only factors from the blocks health, work and social environmental characteristics remained. In the final model, better physical health, >2 days/week intensively physically active, higher body height and working in healthcare predicted working beyond retirement. If respondents had a permanent contract or worked in handcraft, or had a partner that did not like them to work until the official retirement age, they were less likely to work beyond retirement. Area under the curve was 73% (p<0.05). Explained variance was 18.3%. Internal validation led to an area under the curve of 68%. Conclusion: Health, work characteristics and social environment predicted working beyond retirement, but register-based socioeconomic and demographic characteristics did not independently predict working beyond retirement. This study shows that working beyond retirement is multifactorial.